PENERAPAN EVIDENCE BASED NURSING AKUPRESUR PERIKARDIUM 6 PADA IBU HAMIL DENGAN HIPEREMESIS GRAVIDARUM (HEG) DI RS BHAYANGKARA TK.I R. SAID SUKANTO - Anisa Nurhazyima, (2022)
Pregnancy is a physiological process experienced by women starting from the fertilization process, the development of the fetus in the womb to the birth process. Pregnant women during pregnancy will experience physiological and psychological changes. One of the changes in early pregnancy is nausea and vomiting. About 20-30% have hyperemesis gravidarum. The cause of nausea and vomiting in pregnant women is associated with an increase in the hormone estrogen and HCG (Human Chorionic Gonadotropin). One of the non-pharmacological therapies to treat nausea and vomiting is acupressure at the Pericardium 6 (P6) point. Stimulation at this point can increase the release of beta-endorphins in the pituitary and adrenocorticotropic (ACTH) along the chemoreceptor trigger zone (CTZ) which can inhibit the vomiting center. Objective: to determine the effect of acupressure at the Pericardium 6 point on the intensity of nausea and vomiting in first trimester pregnant women. This study used the literature review method with the application of evidence based nursing in nursing care for two patients with hyperemesis gravidarum.The instrument used to measure nausea and vomiting in pregnant women uses PUQE (Pregnancy Unique Quantification of Emesis-24). Results: there was a change in the intensity of nausea and vomiting felt by pregnant women in the first trimester after acupressure was applied to the pericardium point 6 from a score of NVP 13 to NVP 4 Keywords: Hyperemesis Gravidarum, Acupressure P6, Pregnant Women